1995
DOI: 10.1177/089270579500800103
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Filament Wound Graphite/Thermoplastic Composite Ring-Stiffened Pressure Hull Model

Abstract: The design, analysis, manufacture, and hydrostatic testing results of a 24- inchdiameter ringstiffened pressurehull model are presented. The AS-4 graphite/PEEK cylinder is manufactured using a nonautoclave insitu filament winding and tape laydown process. The cylinder incorporates 5 hoopwound rings and a shell (hoop/axial construction) that are integrally wound during manufacture. Ultrasonic inspection in conjunction with optical microscopy of end rings indicates that high quality is achieved with a void conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Better quality raw thermoplastic tapes, especially with constant ply thickness, fewer intralaminar voids and good fibre/matrix distribution, would be also beneficial for optimal lamination and final quality of the laminates, as also concluded by other investigations. 33,34,54,57 The use of re-passes may also be of assistance for a better final laminate quality. Thus, further research focused on the investigation of different material grade and different lamination strategies for the improvement of the quality of ISC laminates is proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better quality raw thermoplastic tapes, especially with constant ply thickness, fewer intralaminar voids and good fibre/matrix distribution, would be also beneficial for optimal lamination and final quality of the laminates, as also concluded by other investigations. 33,34,54,57 The use of re-passes may also be of assistance for a better final laminate quality. Thus, further research focused on the investigation of different material grade and different lamination strategies for the improvement of the quality of ISC laminates is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies indicated the need of higher quality raw prepreg tapes for decreasing the final void content, therefore increasing the mechanical properties closer to autoclaved levels. 33,34 Higher quality thermoplastic tapes may consist of low intralaminar void content, good fibre and matrix distribution and parallel surfaces. In the meanwhile, low deposition speed, high compaction forces, good lay-up strategies, self-heated tools and a proper temperature control are generally proposed to address good quality thermoplastic parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies developed composite pressure vessels with thin to intermediate wall thickness and radiusto-thickness ratios of greater than ten, for example see [2,3,5,6]. Several thick-wall pressure vessels were designed, manufactured, and tested and found to fail prematurely [7] due to the lack of understanding of thick-section composite structures' mechanical behavior, effects of the end-caps, and/or manufacturing issues.…”
Section: Introductionmentioning
confidence: 97%
“…That study concentrated on tape placement and several carbon reinforced thermoplastics were examined including PPS, PEI, PEEK, and PEKK, and a number of cylinders were tested [4][5][6]. Further details of the thermoplastic composite tape placement technique were presented recently [7].…”
Section: Introductionmentioning
confidence: 99%